2022
DOI: 10.1021/acs.jmedchem.2c01457
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ferroptosis in Glioblastoma and Ovarian Cancers by a New Pyrrole Tubulin Assembly Inhibitor

Abstract: We synthesized new aroyl diheterocyclic pyrrole (ARDHEP) 15 that exhibited the hallmarks of ferroptosis. Compound 15 strongly inhibited U-87 MG, OVCAR-3, and MCF-7 cancer cells, induced an increase of cleaved PARP, but was not toxic for normal human primary T lymphocytes at 0.1 μM. Analysis of the levels of lactoperoxidase, malondialdehyde, lactic acid, total glutathione, and ATP suggested that the in vivo inhibition of cancer cell proliferation by 15 went through stimulation of oxidative stress injury and Fe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Sulfonamides 10−13 were prepared as depicted in Scheme 1. 3-Aroylpyrroles 10 and 11 were synthesized starting by reaction of ketones 22 or 23 34 with the 2-(trimethylsilyl)ethoxymethyl (SEM) protected 4-bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (24) in the presence of copper(I) iodide, cesium carbonate, and 1,10-phenanthroline under microwave irradiation at 210 °C, 200 W for 40 min to give 4-(3-benzoyl-1H-pyrrol-1-yl)-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)-benzenesulfonamide (27) or the corresponding 3-(3′,4′,5′-trimethoxybenzoyl-1H-pyrrol-1-yl) derivative (28). Similarly, 29 and 30 were obtained starting from 23 and 3-bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (25) or 2bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (26), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sulfonamides 10−13 were prepared as depicted in Scheme 1. 3-Aroylpyrroles 10 and 11 were synthesized starting by reaction of ketones 22 or 23 34 with the 2-(trimethylsilyl)ethoxymethyl (SEM) protected 4-bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (24) in the presence of copper(I) iodide, cesium carbonate, and 1,10-phenanthroline under microwave irradiation at 210 °C, 200 W for 40 min to give 4-(3-benzoyl-1H-pyrrol-1-yl)-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)-benzenesulfonamide (27) or the corresponding 3-(3′,4′,5′-trimethoxybenzoyl-1H-pyrrol-1-yl) derivative (28). Similarly, 29 and 30 were obtained starting from 23 and 3-bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (25) or 2bromo-N,N-bis((2-(trimethylsilyl)ethoxy)methyl)benzenesulfonamide (26), respectively.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Sulfonamides 14−21 were prepared by similar routes, as depicted in Scheme 2. Compounds 14−17 were synthesized starting from 3-aroyl-4-phenylpyrroles 31 35 and 32 34 (Scheme Biology. Inhibition of hCA I, hCA II, hCA IX, and hCA XII Isoforms.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there are few studies on the function of TUBE1. Tubulin is thought to be stimulated of oxidative stress injury and Fe 2+ accumulation, which displays inhibition of cancer cell proliferation 24 . Moreover, blocking tubulin-dependent mitochondrial depolarization could enhance ROS formation and ROS-related mitochondrial dysfunction like erastin do 25 .…”
Section: Discussionmentioning
confidence: 99%
“…[ 40 ] Together with VEGF, CD31 is a well‐defined angiogenic marker and shows high expression on the surface of endothelial cells, which is implicated with angiogenesis in many types of cancer, such as breast cancer, [ 41 ] glioblastoma, and ovarian cancer. [ 42 ] It has been demonstrated that the impact of lactic acid on tumor angiogenesis is the consequence of the interaction between vascular endothelial cells and tumor cells. [ 43 ] Our findings illuminated that both lactate and glucose stimulation counteracted the suppressive effect of FGF6 depletion on the viability, migratory ability, and tube formation of HUVECs cocultured with BC cell supernatants and tube formation capacity of BC cells.…”
Section: Discussionmentioning
confidence: 99%